Concomitant variability of the central sulcus morphology and adjacent connectivity patterns - Lefranc, S.; Sun, Z. Y.; Roca, P.; Poupon, C.; Le Bihan, D.; Mangin, J.-F; Riviere, D. (Proceedings (International Symposium on Biomedical Imaging), 2015)
Coupling the morphological characteristics of sulcal anatomy with connectivity patterns established from diffusion MRI remains a major challenge. Individual results from a group-wise connectivity-based parcellation of the cortex in the brain central region are compared with cortical folding. This comparison uses an original approach wich allows to represent the main inter-individual variability bringing closer subjects with similar central sulcus shape. Data stemming from several modalities - here connectivity and morphology - can thus be compared with a restrained inter-subject variability on similar subjects. Our approach demonstrates that the lowest position of the hand knob of the central sulcus, known to be related to the hand motor region, is correlated with the structural parcellations of adjacent gyri. These results strenghten the validity of our connectivity-based parcellation, and opens the way to multimodal neuroscientific validation.